2010
DOI: 10.1120/jacmp.v11i2.2913
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characteristics of an electron multileaf collimator for modulated electron radiation therapy

Abstract: Modulated electron radiation therapy (MERT) has been proven as an effective way to deliver conformal dose distributions to shallow tumors while sparing distal critical structures and surrounding normal tissues. It had been shown that a dedicated electron multileaf collimator (eMLC) is necessary to reach the full potential of MERT. In this study, a manually‐driven eMLC for MERT was investigated. Percentage depth dose (PDD) curves and profiles at different depths in a water tank were measured using ionization ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…(2) IMET is similar, in concept, to inverse treatment planning (or optimization) of IMRT and uses multiple, optimally-weighted beamlets to deliver dose conformal to the PTV. (3) Beamlets are shaped by a conventional photon multileaf collimator (pMLC), (4)(5)(6)(7)(8) specific add-on electron multileaf collimator (eMLC), (9)(10)(11)(12)(13) or few-leaf electron collimator (FLEC). (14,15) Though the MERT techniques show promising results in terms of PTV coverage and normal tissue sparing, they are complex in clinical implementation and dose delivery, thus compromising the efficiency of treatment.…”
mentioning
confidence: 99%
“…(2) IMET is similar, in concept, to inverse treatment planning (or optimization) of IMRT and uses multiple, optimally-weighted beamlets to deliver dose conformal to the PTV. (3) Beamlets are shaped by a conventional photon multileaf collimator (pMLC), (4)(5)(6)(7)(8) specific add-on electron multileaf collimator (eMLC), (9)(10)(11)(12)(13) or few-leaf electron collimator (FLEC). (14,15) Though the MERT techniques show promising results in terms of PTV coverage and normal tissue sparing, they are complex in clinical implementation and dose delivery, thus compromising the efficiency of treatment.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The E-MLC would be attached either on an existing electron applicator or on a retractable applicator. A second approach 9-12 is to use the photon MLC for the collimation of electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…Various groups [1][2][3][4][5] have reported on the feasibility of using the photon MLC as a possible collimation device, while others [6][7][8][9][10][11][12] have manufactured add-on electron MLCs that are positioned closer to the patient in an effort to minimize the penumbra width due to air scatter. It was reported that acceptable penumbra can be obtained with photon MLCs by using SSDs in the 70 cm range.…”
Section: Introductionmentioning
confidence: 99%